Persfektif Pemasaran Global dalam Bisnis Internasional - Devina Wistiasari; Defen Defen; Deviana Lie; Jason Jason; Jesty Jesty; Jolin Jolin (Universitas 17 Agustus 1945, 2022)
AbstractThe global marketing perspective in international business is a necessary approach for companies operating in global markets. In the era of globalization, international business must understand and manage the challenges and opportunities that arise in the international market. Global marketing involves different strategies and tactics than domestic marketing, given the differences in culture, language, consumer preferences, and regulations in each country. This research aims to provide an overview of marketing in international business and to organize and classify the literature on marketing to clarify the importance of this tool and encourage future research in international business marketing (IBM) projections and the ubiquity of this tool's power in the hands of users. This research also focuses on companies that must be able to adapt their products and marketing messages to local preferences and the needs of consumers in each market and must have in-depth knowledge of international trade laws and regulations and develop effective cross-cultural communication skills. The global marketing perspective in international business is the key to a company's success in the global market. In an increasingly connected world, companies must be able to understand global markets, adapt their products and strategies, face existing challenges, and forge strategic partnerships. With the right approach, companies can achieve a competitive advantage in an increasingly complex global marketplace. Apart from that the contribution of research is also important to identify new challenges and opportunities for marketers, researchers and international companies and in terms of unraveling the existing contradictions, applying new theoretical frameworks to make better future decisions for large corporations, and providing higher quality research to new in the IBM context.